1989
DOI: 10.1128/aem.55.4.959-964.1989
|View full text |Cite
|
Sign up to set email alerts
|

Population Size and Distribution of Rhizobium leguminosarum bv. trifolii in Relation to Total Soil Bacteria and Soil Depth

Abstract: Bacterial cells small enough to pass through 0.4-,um-pore-size filters made up 5 to 9% of the indigenous bacterial population in 0to 20-cm-depth samples of Abiqua silty clay loam. Within the same soil samples, cells of a similar dimension were stained with fluorescent antibodies specific to each of four antigenically distinct indigenous serogroups of Rhizobium leguminosarum bv. trifolii and made up 22 to 34% of the soil population of the four serogroups. Despite the extensive contribution of small cells to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Soil samples were collected from a depth of 0 to 5 cm from a silty clay loam of the Abiqua series (Cumulic Ultic Haploxeroll) under permanent pasture. The physical and chemical characteristics of the soil have been described elsewhere (1,7). By using a soil tube auger, 20 soil cores were removed from within each of six grids (1 by 1 m) spaced 20 m apart along a transect running diagonally across the pasture.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Soil samples were collected from a depth of 0 to 5 cm from a silty clay loam of the Abiqua series (Cumulic Ultic Haploxeroll) under permanent pasture. The physical and chemical characteristics of the soil have been described elsewhere (1,7). By using a soil tube auger, 20 soil cores were removed from within each of six grids (1 by 1 m) spaced 20 m apart along a transect running diagonally across the pasture.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were passed through 25-mm-diameter, 0.4-p.m-poresize Sudan black-stained polycarbonate membranes (Nuclepore Corp., Pleasanton, Calif.). Filters were destained with citrate buffers and prepared for epifluorescence microscopy as described elsewhere (7).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For 70 years serotyping has been used to monitor root nodule occupancy by antigenically distinct strains of Bradyrhizobium and Rhizobium species (1,5,6,18,22,39). Serotyping allows researchers to gain a superficial picture of the diversity within native rhizobial populations at specific sites, to track the occurrence and distribution of antigenically related bacteria across states, countries, and continents, and to study the autecology of these bacteria in soil (4,7,13,15,17,30,33,36,38,40,42,49,53). Studies carried out with Bradyrhizobium japonicum (24,34,35,43,50,51,54) and Rhizobium leguminosarum (8,19,55) have shown that individual serotypes can be composed of nonidentical strains.…”
mentioning
confidence: 99%